Disease-resistant varieties of Chinese cabbage (Brassica rapa L. ssp. pekinensis) inhibit Plasmodiophora brassicae infestation by stabilising root flora structure - Fang, Tianyi; Han, Xueyu; Yue, Yanling (Frontiers in Plant Science, 2024)
The application of disease-resistant varieties is the most cost-effective method for solving the problem of clubroot. "Shangpin," a disease-resistant variety of Chinese cabbage with broad-spectrum immunity to Plasmodiophora brassicae (P. brassicae), was screened in a previous study. Based on 16S rRNA sequencing technology, we annotated the compositional differences between the rhizosphere, rhizoplane, and endosphere bacterial communities of "Shangpin" and "83-1" under P. brassicae stress.Alpha diversity analysis showed that the abundance of microorganisms in the root system of "83-1" changed more than that of "Shangpin" after P. brassicae infestation, and Beta diversity analysis indicated that Flavobacterium and Sphingomonas may mediate clubroot resistance, while Nitrospira, Nitrosospira, and Pseudomonas may mediate P. brassicae infestation among the bacteria in the Top 10 abundances.Microbial functional analyses showed that the root microorganisms of "83-1" were metabolically weakened after P. brassicae inoculation and were inhibited in competition with pathogenic bacteria. Conversely, the root microorganisms of "Shangpin" maintained the strength of their metabolic capacity, which took a favorable position in competition with the pathogen and inhibited the growth and development of the pathogen, thus showing resistance. Root secretions of "Shangpin" significantly inhibited the incidence and disease index of clubroot, which indicated that under clubroot stress, resistant varieties maintain root microbial diversity and microbial community functions through specific root exudates, enriching the genera Flavobacterium and Sphingomonas, thus showing resistance. The results of this study reveal the resistance mechanism of resistant varieties to clubroot and provide new insights into the prevention and control of clubroot in Chinese cabbage.